ESTUDO ANALÍTICO, AVALIAÇÃO DA TOXICIDADE E ATIVIDADE MOLUSCICIDA DO ÓLEO ESSENCIAL Cinnamomum zeylanicum Blume (CANELA) FRENTE AO CARAMUJO Biomphalaria glabrata (Say,1818) - Reis, Jonas Batista (2012)
The use of plants for medicinal purposes is an ancient practice. Among various species of plants containing essential oils in its composition and that may be used to fight various diseases highlight the essential oil extracted from the leaves of cinnamon (Cinnamomum zeylanicum Blume). The cinnamon oil can be used to prevention of schistosomiasis, an endemic disease that affects areas with poor basic sanitation. In this study, the essential oil was extracted from the leaves of cinnamon by hydrodistillation and its molluscicidal action has been assessed against the snail Biomphalaria glabrata (Say, 1818). The percentage of oil in the leaves was an average of 1.3 mL in the time interval ranging from 1 to 5 hours, after extraction the physico-chemical properties of oil were determined. The measurements of oil components were made by gas chromatography-mass spectrometry (GC-MS). The chromatographic analysis showed that oil has 82.67% of eugenol (major constituent), at retention time 22,63 min and 2.47% of humulene (minor component), at retention time 25.74 min. The cinnamon oil has been tested for toxicity and molluscicidal agent, calculating the lethal concentration (LC50). As for toxicity, the oil extracted from cinnamon leaf was considered moderately toxic LC50 = 162.1 mg.L-1 ± 2,80, with a confidence interval 95%. For the pilot test, the molluscicide activity of the oil presented a mortality of 100% in 72 h indicating the presence of toxic compounds in the oils against the snail indicating the presence of toxic compounds in the oils against the snail. The molluscicide activity of essential oil extracted from the leaves of cinnamon obtained results relative to the 50% lethal concentration LC50 of 18.62 mg L-1 ± 2,18, with a confidence interval 95%, lower the level recommended by the World Health Organization (WHO), showing that this oil is active against the snail Biomphalaria glabrata.